2022
DOI: 10.3390/jcm11041050
|View full text |Cite
|
Sign up to set email alerts
|

Awakened Beta-Cell Function Decreases the Risk of Hypoglycemia in Pregnant Women with Type 1 Diabetes Mellitus

Abstract: Diabetes in pregnancy creates many problems for both the mother and child. Pregnant women with type 1 diabetes experience more frequent hypoglycemic and hyperglycemic episodes. This study aimed to determine the risk of clinically significant biochemical hypoglycemia (CSBH) by HbA1c, fasting C-peptide, mean plasma glucose (PG), and insulin dose in pregnant women type 1 diabetes mellitus according to each trimester of the pregnancy. Methods. We conducted a prospective observational study of 84 pregnant women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The findings of the study revealed that higher pre-pregnancy HbA1c was a predictive factor for poor glycemic control through-out the entire pregnancy [74]. Maintaining blood glucose and HbA1c levels within a target range before pregnancy is crucial to reduce the risk of complications [32,75,76]. The comprehensive evaluation for women with diabetes considering pregnancy should include a thorough review of their medical history, including previous pregnancies and comorbidities [77].…”
Section: Evaluation During Preconceptionmentioning
confidence: 99%
“…The findings of the study revealed that higher pre-pregnancy HbA1c was a predictive factor for poor glycemic control through-out the entire pregnancy [74]. Maintaining blood glucose and HbA1c levels within a target range before pregnancy is crucial to reduce the risk of complications [32,75,76]. The comprehensive evaluation for women with diabetes considering pregnancy should include a thorough review of their medical history, including previous pregnancies and comorbidities [77].…”
Section: Evaluation During Preconceptionmentioning
confidence: 99%